SISTEM INFORMASI MONITORING KUALITAS UDARA BERBASIS INTERNET OF THINGS DENGAN METODE FUZZY MAMDANI - Alvin Mubarok, Muhamad; Chamdan Mashuri (Inovate, 2025)
Air quality is an important factor that affects human health, especially in densely populated urban areas. This research aims to develop an Internet of Things (IoT)-based air quality monitoring information system using the Fuzzy Mamdani method. The problem faced is the lack of an air quality monitoring system that can provide real-time data in Jombang Square, which is an area with a high level of vehicles. The method used in this study is Fuzzy Mamdani, which allows the processing of data from sensors to determine the air quality category, which is good, bad, or harmful. The system uses an ESP-12 NodeMCU microcontroller, an MQ-135 sensor to detect carbon monoxide (CO), and a DHT11 sensor to measure temperature and humidity. The collected data will be analyzed and displayed in real-time through the blynk app, which also notifies users when the air quality reaches dangerous levels. The test results showed that the system was able to classify air quality with good accuracy, with an average Mean Absolute Error of 0,4%. This system has proven to be effective in providing accurate and responsive information about air quality conditions, so that it can be used as a tool in decision-making related to public health.